Authenticity of Identity in Lauren Oyler's Fake Accounts - Singh , Raj Kishor (Journal of Innovation in Academia, 2025)
This study explores authenticity in Lauren Oyler’s Fake Accounts through the lens of Goffman’s self-presentation theory, Baudrillard’s simulacra and hyperreality, and Turkle’s insights on digital disembodiment. It analyzes the protagonist’s negotiation of online and offline identities, revealing how digital personas operate as curated performances detached from an underlying “real” self. Using Goffman’s dramaturgical model, the study shows how social media fosters continuous impression management similar to theatrical role-playing. Baudrillard’s concept of hyperreality further exposes these digital identities as simulacra, self-referential images that supplant authenticity. Turkle’s framework highlights the alienation and fragmentation arising from fragmented digital selves. Together, these theories illuminate the novel’s critique of performative pressures and the crisis of authenticity in hyperconnected, postmodern digital culture. Ultimately, Fake Accounts questions the possibility of genuine selfhood amid pervasive simulation and digital disembodiment.